Nahdlatul Ulama dan Kristenisasi Di Desa Tegalombo Pati Tahun 1970-2009: Nahdlatul Ulema and Christianization in Tegalombo Pati Village, 1970-2009 - Fajarul, Ahmad Anas (Journal of Islamic History, 2022)
Through a historical approach, this research reveals the process of forming Christian bases in Tegalombo Village and how the process of social-religious transformation of the community occurred after the establishment of the Nahdlatul Ulama (NU) branch in Tegalombo. The results of the study found that NU succeeded in countering Christianization by establishing various Islamic educational institutions such as PAUD, RA, TPQ, and MI. Nahdlatul Ulama was also involved in the events of resolving tensions between Islam and Christianity and building religious tolerance in Togalombo. Tensions between Muslims and Christians in Tegalombo that have occurred, namely tensions in 1942, tensions, tensions at the 1996 recitation event, and tensions at the 2009 KKR event. After 2009, the life of Muslims and Christians went harmonious, even Nahdlatul Ulama and Christians always cooperate in various activities.